Development of Interactive Learning Media on Network Service Technology Subjects Class XI TKJ - Hidayat Saputra; Heri Mulyono; Regina Ade Darman (Universitas Trunojoyo Madura, 2022)
This study aims to develop interactive learning media using articulate storylines on network service technology subjects in class XI that meet valid and practical criteria. This research uses the Research and Development (R and D) research method with the ADDIE development model with five stages (analysis, design, development, implementation, and evaluation). The population in this study were students of class XI TKJ at SMKN 2 Padang who were involved in the subject of network service technology, with a total sampling technique of sampling. The instruments used in this research are validity instruments and practicality instruments. Based on the results of the validity of the material and media, the results obtained are material validation with an average value of 0,902 with a